2019
DOI: 10.1007/s10948-019-05312-4
|View full text |Cite
|
Sign up to set email alerts
|

A Personal Perspective on the Unconventional Superconductivity of Sr2RuO4

Abstract: I give a personal account of the unfolding story of the unconventional superconductivity of Sr 2 RuO 4. This is a subject of topical importance in light of recent measurements that suggest that its order parameter may be even parity, contrary to the picture that had built up over the course of over two decades of research. With an eye on the past, I stress the generous encouragement that I received from Ted Geballe in the early years of my Sr 2 RuO 4 research. Looking to the future, I give my opinion about why… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Sr 2 RuO 4 is widely recognized as the paradigmatic example of a very clean, strongly correlated Fermi liquid (FL) with a simple quasi-two-dimensional Fermi surface (FS), from which an unconventional superconducting ground state emerges 1,2 . While the superconducting state has been a subject of intense study [3][4][5] , there are multiple attributes of Sr 2 RuO 4 that motivate an in-depth analysis of the normal state, including the ability to characterize the FL state and quasiparticle dispersions with exquisite accuracy and the opportunity to study how the quasiparticles gradually lose coherence as temperature T is raised, evolving all the way into 'bad metal' behavior at high-T [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Sr 2 RuO 4 is widely recognized as the paradigmatic example of a very clean, strongly correlated Fermi liquid (FL) with a simple quasi-two-dimensional Fermi surface (FS), from which an unconventional superconducting ground state emerges 1,2 . While the superconducting state has been a subject of intense study [3][4][5] , there are multiple attributes of Sr 2 RuO 4 that motivate an in-depth analysis of the normal state, including the ability to characterize the FL state and quasiparticle dispersions with exquisite accuracy and the opportunity to study how the quasiparticles gradually lose coherence as temperature T is raised, evolving all the way into 'bad metal' behavior at high-T [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been speculated 2 to be a long sought metallic analogue of superfluid helium-3 ( 3 He), and the possibility of triplet superconductivity has been explored by various groups (see Ref. [3][4][5][6][7], and references therein). Theoretically, it was found that the free energy differences between different possible pairing symmetries were so small as to be nearly degenerate, rendering it a far from trivial problem to predict the pairing symmetry 5 , a situation exacerbated by the large number of symmetrydistinct superconducting order parameters 8 compatible with the body centred tetragonal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetry of the order parameter is still a debated question, with recent experiments challenging established views [4,5] for recent reviews and discussion see e.g. [6][7][8].…”
Section: Introductionmentioning
confidence: 99%